Rewrite to reread: ¡Mío cid! by Orejudo, Martín and Reig (XXI Century. Spanish Literature and Culture, 2016)
This work is dedicated to the analysis of ¡Mio Cid! (2007), a singular rewriting of the Cantar de mio Cid developed by Antonio Orejudo, Luisgé Martín and Rafael Reig. The objective is to examine the contextual factors that justify its appearance and to identify the different degrees of hypertextual dependence that each one of its parts establishes with Medieval antecedent.
Keywords: Cid; Cantar de Mío Cid; Rewriting; ypertextuality; Hypertextuality; Posmodernity